Efficacy and Safety of Integrated Traditional Chinese Medicine and Western Medicine on the Treatment of Rheumatoid Arthritis: A Meta-Analysis - Zhou, Xueping; Yu, Zhichao; Fu, Ling; Xing, Qi (Evidence-based complementary and alternative medicine, 2020)
Objective. Integrated therapy of traditional Chinese medicine (TCM) and Western medicine (WM) has gradually been applied to the treatment of rheumatoid arthritis (RA). Recently published studies have provided a wealth of data and information about the effectiveness of combination treatments, but high-quality evidence-based meta-analysis on this issue is not available yet. This study was conducted to compare and evaluate the efficacy and safety of the integrated therapy for RA. Methods. PubMed, EMBASE, and the Cochrane Library were searched up to January 2020. Randomized controlled trials (RCTs) that compared the efficacy and safety of integrative TCM-WM with WM alone for RA were included. The outcome measures contained therapeutic effects (TEs), tender joint count (TJC), swollen joint count (SJC), duration of morning stiffness (DMS), grip strength (GS), disease activity score in 28 joints (DAS28), rheumatoid factor (RF), anti-cyclic peptide containing citrulline (anti-CCP), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and adverse events (AEs) to assess the efficacy and safety of different treatments. Results. A total of 20 RCTs with 2269 patients met the inclusion criteria. TCM used in these studies included Chinese herbal decoctions and tablets or capsules made from herbs and their extracts, while WM included disease-modifying antirheumatic drugs (DMARDs), nonsteroidal anti-inflammatory drugs (NSAIDs), and glucocorticoids (GC). Compared with patients receiving WM treatment alone, patients with integrative TCM-WM treatment showed better TEs (OR = 3.03, 95% CI [2.36, 3.88]). The integrative treatment group showed reductions in TJC (MD = −1.17, 95% CI [−2.12, −0.21]), SJC (MD = −0.87, 95% CI [−1.85, 0.10]), DMS (SMD = −0.69, 95% CI [−0.98, −0.41]), DAS28 (MD = −0.43, 95% CI [−0.57, −0.29]), RF (SMD = −0.59, 95% CI [−0.91, −0.27]), anti-CCP (SMD = −0.21, 95% CI [−0.36, −0.06]), ESR (MD = −8.36, 95% CI [−12.60, −4.12]), and CRP (MD = −6.73, 95% CI [−9.38, −4.08]), and increment in GS (SMD = 0.12, 95% CI [−0.63, 0.87]). AEs, especially gastrointestinal disorders, abnormal liver function, leukopenia, skin allergies and rashes, headaches and dizziness, and alopecia, significantly decreased (OR = 0.37, 95% CI [0.29, 0.47]) in the integrative treatment group. Conclusions. The findings of this meta-analysis indicate that integrative TCM-WM could obtain effective and safe results in the treatment of RA. Using TCM as an adjunctive therapy in RA has great prospects for further development.